Santri-edupreneur: Empowerment of students of Al-ikhlas Islamic Boarding School Kubu Raya through quail waste management to realize a sustainable economy - Nawawi, Nawawi; Bahri, Saiful; Siswandi, Siswandi (Universitas Ahmad Dahlan, 2024)
Al-Ikhlas Kubu Raya Islamic Boarding School faces challenges in managing quail farming enterprises, particularly in the areas of digital marketing, entrepreneurial skills, and waste management. The primary obstacles are the inability to utilize modern technology, as well as the limited ability of students and ustadz in business management. This program aims to empower students and entrepreneurs by providing entrepreneurship training and internet marketing skills, as well as introducing biodigester technology for converting poultry waste into biogas. The methods of implementation consist of socialization, problem identification, entrepreneurship training, marketing through Shopee and TikTok, and support in the use of biodigesters. The entrepreneurial skills of students and Ustadz improved by 85%, while product marketing via digital channels enhanced sales by up to 80%. Islamic boarding schools have successfully implemented biodigester technology, converting waste into renewable energy with a 60% success rate. This program has effectively enhanced the economic autonomy of Islamic boarding schools by optimizing livestock enterprises and implementing technology-driven waste management, resulting in beneficial effects on both the economy and the environment.